Service providing scenario of urban primary health care services delivery project working in selected municipality - Reza, Hasan M.; Sarkar, M. Abdul M. (International Journal Of Community Medicine And Public Health, 2019)
Background: The urbanization and urban growth is going through very rapid in Bangladesh. This growth is being fuelled by rising incomes due to rapid expansion of commerce and industry. The rapid and incessant growth of urbanization on Kushtia district is creating continuous pressure on urban health care services. Urban poor people are also a vital factor for promoting urban primary health care services delivery project (UPHCSDP) to provide health care facilities. Methods: A cross sectional survey was carried out among 576 patients in 3 selected urban primary health care centres in Kushtia Municipality with a major concentration of people residing in urban areas. Data were collected using questionnaires regarding type of care or treatment patients demanded and type of care they received from the clinic. Results: Study results showed that total of 46.5% of the subjects demanded maternal and obstetric health services and 8.6% demanded child health diagnosis and care. It was found that a total of 22.0% of the subjects received physical diagnosis from the centres. About 7.1% clients received advice or suggestions and 8.0% received normal delivery service from the centres. Conclusions: The result shows that these clinics provide a lot of health care services to the clients especially on maternal and child health care delivery system. These services are provided to the patient with less or free of cost. Study exhibited that the overall health care services of health care centres are good. The clients come to these centres for the good quality of treatment.